Enhancing Energy Efficiency: Geothermal Heat Pumps Utilizing Existing Water Boreholes in Pakistan - Saif Ullah; Muhammad Irfan; Muhammad Mahabat Khan (Engineering Proceedings, 2023)
Vertical borehole geothermal heat pumps (GHPs) offer eco-friendly and energy-efficient heating and cooling. This paper proposes enhancing the coefficient of performance (COP) by converting air source heat pumps (ASHPs) into ground source heat pumps (GSHPs). This study presents a cost-effective approach to utilizing existing water boreholes in Pakistani buildings, reducing drilling and piping expenses. The results show that GSHPs achieved average COP values of 5.92, 33.33% higher than ASHPs. GSHPs demonstrated an average energy efficiency ratio (EER) of 20.12, exceeding ASHPs by 33.9%. These findings highlight the enhanced COP and energy efficiency of GSHPs, making them an attractive option for sustainable HVAC systems.